2006
DOI: 10.1161/01.hyp.0000197953.91461.95
|View full text |Cite
|
Sign up to set email alerts
|

Low Muscular Mass and Overestimation of Microalbuminuria by Urinary Albumin/Creatinine Ratio

Abstract: Abstract-Microalbuminuria is a mild urinary albumin elevation and is associated with cardiovascular disease. Urinary albumin/creatinine ratio is recommended for microalbuminuria assessment, because it reflects urinary albumin excretion. Muscular mass could affect albumin/creatinine ratio, because urinary creatinine reflects muscular mass. The study investigated high albumin/creatinine ratio attributed to low urinary creatinine without microalbuminuria. The Gubbio Population Study for ages 45 to 64 collected da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…Prior studies demonstrated that spot-ACR is more likely to misclassify patients with lower muscle mass as having microalbuminuira (28). Similarly, at the same level of albuminuria, women have higher spot-ACR than do men (20,29,30).…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies demonstrated that spot-ACR is more likely to misclassify patients with lower muscle mass as having microalbuminuira (28). Similarly, at the same level of albuminuria, women have higher spot-ACR than do men (20,29,30).…”
Section: Discussionmentioning
confidence: 98%
“…Advanced chronic kidney disease may be associated with a decrease in lean body mass leading to a low creatinine excretion rate. This may lead to a decreased performance of the UACR test if the same cutoffs as those used for the general population are used (29). The study presented here shows that this is not the case in the renal transplant population studied and that the 17-and 25-mg/g cutoffs for men and women proposed by previous investigators and adopted as an option by some guidelines for the general and diabetic population seem appropriate for the renal transplant population.…”
Section: Performance Measures Of Uacr For the Detection Of Albuminurimentioning
confidence: 67%
“…[25][26][27] Urinary creatinine excretion was used as marker of creatinine generation. 28 Serum total calcium was expressed with correction for serum albumin concentration. 29 Acute kidney injury was defined as doubling of baseline serum creatinine or halving of baseline eGFR or low urine output.…”
Section: Methodsmentioning
confidence: 99%
“…The practical implications of the study are potentially relevant to the subgroup of hypertensives with eGFR<60 mL/ min×1.73 m 2 (ie, to a subgroup of hypertensives who account for ≤20% of hypertensives in the general population). 28,40 Within the group of hypertensives with low kidney function, the antihypertensive effect of chlorthalidone was more constant for SBP than for DBP and did not associate with adverse events in patients with higher body mass index. Thus, data point to a favorable benefit/risk ratio of chlorthalidone in patients with low kidney function, systolic hypertension, and overweight.…”
Section: Perspectivesmentioning
confidence: 95%